2018
DOI: 10.1101/254144
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The yeast GRASP Grh1 displays a high polypeptide backbone mobility along with an amyloidogenic behavior

Abstract: 17GRASPs are proteins involved in cell processes that seem paradoxical, such as being responsible 18 for shaping the Golgi cisternae and also involved in unconventional secretion mechanisms that 19 bypass the Golgi, among other functions in the cell. Despite its involvement in several relevant 20 cell processes, there is still a considerable lack of studies on full-length GRASPs. Our group has 21 previously reported an unexpected behavior of the full-length GRASP from the fungus C. showing that is also observe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(41 citation statements)
references
References 56 publications
8
33
0
Order By: Relevance
“…and the transition to the unfolded state is linear, just like the one observed before for the full‐length CnDGRASP . The data indicate that the overall tertiary contacts of DGRASP65 share some of the structural features of the lower eukaryotes DGRASPs, which were previously attributed to be collapsed IDPs/molten globule‐like proteins .…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…and the transition to the unfolded state is linear, just like the one observed before for the full‐length CnDGRASP . The data indicate that the overall tertiary contacts of DGRASP65 share some of the structural features of the lower eukaryotes DGRASPs, which were previously attributed to be collapsed IDPs/molten globule‐like proteins .…”
Section: Resultssupporting
confidence: 80%
“…ScDGRASP is the one that has the most different and unusual pattern. At pH 3-4, this protein has a huge conformational change in the bsheet-rich structure, previously observed for the fulllength ScGRASP and associated with the formation of a fibril-like supramolecular structure [39]. These data suggest that fibril formation might also take place with the isolated ScDGRASP at lower pHs, although this behavior was not observed for any other GRASP so far and it seems to be unique to yeasts.…”
Section: Dgrasps Show Different Behavior Upon Ph Variationmentioning
confidence: 58%
See 2 more Smart Citations
“…In a previous report, we showed that GRASPs from the fungal pathogen C. neoformans [28] and S. cerevisiae [35] present structural features usually observed in molten globule proteins, even in the absence of any mild denaturing conditions. As expected for a collapsed intrinsically disordered protein, many physicochemical perturbations induced by the crystal packing, (including local dehydration and changes in the dielectric constant, along with increased PEG concentration used in the crystallographic reservoir), promote disorder-to-order transitions in GRASPs [35,36]. Even though GRASPs appear to have a special affinity for divaline-containing C-terminal proteins [27], the overall sequences of their protein partners do not have a conserved sequence or structural feature in common ( Figure S1), suggesting GRASPs might be highly promiscuous in terms of protein-protein interactions.…”
Section: Introductionmentioning
confidence: 83%